An Annotated List of the Lichen Forming Fungi of the Crimean Nature Reserve (CHORNOMORSKI BOTANICAL JOURNAL, 2006)
The list of the lichen forming fungi of the Crimean nature reserve (AR Crimea, Ukraine) includs 344 species of 128 genera, 46 families, 13 orders. 50 species are revealted to be new for reserve. The lichen ecology, locations and bibliography are reported.
Keywords: lichens, list, Crimean nature reserve, AR Crimea, Ukraine.